Advancements in Magnetic Resonance Imaging: A Systematic Review of Emerging Technologies and Clinical Applications - Alsaedi, Mohammed Hameed; Joman, Fahad Mohammed Hassan; Alraddadi, Abdullah Fayez Mubarak; Alharbi , Hashim Nafea Bin Sunaytan; Al Amry, Marwan Abdullah Rubayyi; Alazhri, Hazim Khalid; Almaghamsi , Mohammed Saleh; Alqubali, Alanoud Abdualaziz; Hwsawy, Wedad Abdul Hamid; Mousa , Fardous Saud (Journal of Ecohumanism, 2024)
Magnetic Resonance Imaging (MRI) has undergone significant advancements in recent years, revolutionizing diagnostic and therapeutic approaches across various medical fields. This systematic review explores the latest technological innovations in MRI, including high-field imaging, AI-enhanced applications, functional MRI, and hybrid systems such as PET-MRI. These advancements have contributed to enhanced diagnostic precision, improved patient outcomes, and expanded clinical applications, particularly in neurology, oncology, cardiovascular imaging, and pediatrics. Despite these developments, challenges such as high costs, accessibility barriers, and the need for skilled expertise persist. This review highlights the clinical potential of emerging MRI technologies while addressing the limitations and proposing future directions to bridge existing gaps, emphasizing their role in personalized and precision medicine.